Assessment of BAEL Freshmen’s Proficiency in Formulaic Language: Basis for a Targeted Video-based Intervention - Merigilda Cando; Melody Bing-iyan; Gwyneth Sildon (Journal of English Language and Pedagogy (JELPA), 2026)
Mastering formulaic language, including idioms, collocations, and phrasal verbs is essential for English language learners to achieve native-like fluency and natural communication. However, learners frequently struggle with these expressions. This study addresses the research gap where these three categories are rarely assessed simultaneously and where multimedia tools are underutilized to bridge specific proficiency deficits. This study aims to assess the current proficiency level of first-year Bachelor of Arts in English Language (BAEL) students at a university in the Philippines and subsequently develop a targeted video-based instructional intervention to address their identified weaknesses. Using a quantitative, descriptive research design, the study utilized a 90-item proficiency test to evaluate the participants. The key findings reveal that while students reached a "Proficient" level in phrasal verbs (M=19.11) and collocations (M=19.06), they were only "Approaching Proficient" in idioms (M=16.51), which emerged as the most difficult category. These results indicate that students possess a foundational but unstable understanding of formulaic language. In response, a video-based intervention titled "Idiom Hub" was developed, grounded in the Cognitive Theory of Multimedia Learning and Dual Coding Theory. This intervention utilizes short, multimodal Facebook Reels to explicitly teach the most challenging idioms identified in the assessment. The study concludes that integrating explicit, context-rich, and multimodal teaching approaches is necessary to improve the figurative and semantic processing skills of second language learners.